Reversible splenial lesion syndrome associated with lobar pneumonia: Case report and review of literature. Issue 39 (September 2016) - Li, Chunrong; Wu, Xiujuan; Qi, Hehe; Cheng, Yanwei; Zhang, Bing; Zhou, Hongwei; Lv, Xiaohong; Liu, Kangding; Zhang, Hong-Liang
Abstract: Background: Reversible splenial lesion syndrome (RESLES) is a rare clinico-radiological disorder with unclear pathophysiology. Clinically, RESLES is defined as reversible isolated splenial lesions in the corpus callosum, which can be readily identified by magnetic resonance imaging (MRI) and usually resolve completely over a period of time. RESLES could be typically triggered by infection, antiepileptic drugs (AEDs), poisoning, etc. More factors are increasingly recognized. Methods and results: We reported herein an 18-year-old female patient with lobar pneumonia who developed mental abnormalities during hospitalization. An isolated splenial lesion in the corpus callosum was found by head MRI and the lesion disappeared 15 days later. Based on her clinical manifestations and radiological findings, she was diagnosed with lobar pneumonia associated RESLES. We further summarize the up-to-date knowledge about the etiology, possible pathogenesis, clinical manifestations, radiological features, treatment, and prognosis of RESLES. Conclusion: This report contributes to the clinical understanding of RESLES which may present with mental abnormalities after infection. The characteristic imaging of reversible isolated splenial lesions in the corpus callosum was confirmed in this report. The clinical manifestations and lesions on MRI could disappear naturally after 1 month without special treatment.